Efektivitas Pemberian Pupuk Organik Dan Interval Penyiraman Leri Terhadap Pertumbuhan Tanaman Bayam Merah (Alternanthera amoena Voss) Dengan Sistem Vertikultur - Putri, Suryani Zulfah Indana, Dra. Aminah Asngad M.Si (2016)
Organic fertilizer and leri water can help plant's growing process more optimum. Red spinach containsmuch nutritions that are needed by our body and have estetic value. Vertikultur is a cultivation planting teknique to optimalize limited yard by using highrise planting system. The purpose of this research is to reveal the implication organic fertilizer, watering interval of leri water and also the best interaction between fertilizer and leri water on red spinach growth. This research uses two factors experiment method. Factor 1 is variety of fertilizer (P0= without fertilizer, P1= cow manure fertilizer and P2= compost fertilizer) and factor 2 is leri watering interval (A0= faucet water, A1= leri water once day, and A2= leri water twice a day), with 9 treatments and 3 times repetition. The observed parameters are stem high, leaves amount and wet weight. The observation is done on the fifth week after planting. The data analysis uses two ways ANOVA. The result shows there is an interaction between fertilizer and leri water on the wet weight, but not on the stem high and leaves amount. P1A1 combination gives the best growth implication on all of parameter, while leri wateringinterval once a day is the best for growing.